2021
DOI: 10.1590/1806-9282.20201149
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of pressure pain threshold on myofascial trigger points in the trapezius muscle of women with chronic neck pain

Abstract: OBJECTIVE:The aim of this study was to evaluate the intra-and inter-rater reliability of pressure pain threshold measurement on myofascial trigger points in the trapezius muscle in women with chronic neck pain.METHODS: This reliability study involved 30 volunteers with neck pain for more than 90 days. The assessment procedures were performed by blinded researchers. Two examiners, who were previously trained in the use of algometry, independently performed two assessments of the pressure pain threshold at two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…Previously published articles revealed that the individuals with higher scores in the pain-related questionnaire and with a higher score of central sensitization showed lower values on PPT; in addition, previous studies consistently demonstrated that there was a moderate to strong correlation between PPT value and disability/pain intensity [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Although valid reference values indicative of a normal and abnormal PPT would aid in the clinical diagnosis of pain, no such reliable values and no published review articles currently exist for neck/shoulder and back pain [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously published articles revealed that the individuals with higher scores in the pain-related questionnaire and with a higher score of central sensitization showed lower values on PPT; in addition, previous studies consistently demonstrated that there was a moderate to strong correlation between PPT value and disability/pain intensity [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Although valid reference values indicative of a normal and abnormal PPT would aid in the clinical diagnosis of pain, no such reliable values and no published review articles currently exist for neck/shoulder and back pain [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PPT values collected from several studies were obtained from varying parts of the body and thus may not be directly comparable [ 22 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. However, using these values, we propose a database of PPTs that could serve as a benchmark for future research with pressure algometers on healthy subjects and subjects with some disease or pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value will be fixed on the equipment screen and noted. Three tests will be performed at each point and the average will be calculated [ 30 ].…”
Section: Methodsmentioning
confidence: 99%